Privacy Perceptions of Twitter Users in Saudi Arabia. - ALAMR, BADR (2018)
The operators of the numerous social networking outlets are very much conscious that their proceeds might upsurge as individuals enlarge their preparedness to reveal personal data regarding themselves. This implies that privacy has become a major concern to most technology users. The way information is used by the social network operators remains a major privacy concern across the globe including in countries such as Saudi Arabia. In view of this background information, this study sought to investigate the perceptions of privacy of Twitter users in Saudi Arabia. The study objectives the study included to assess the understanding of the twitter users (Saudi Arabians) about privacy issues in social network services and their use of privacy settings as the first objective. The second objective was to determine whether the merits of online social interacting overweigh the dangers of sharing private data or the willingness to share data, the third one to examine the significance of twitter in one’s life, and the final one to examine the impact of the understanding of the user of privacy on the data shared over twitter. The optioned for the quantitative path as the research approach since it facilitated the testing of the outlined research hypotheses. The major constructs to this end encompassed age, trust, education, experience, and gender. On the other hand, the dependent variable was the perceptions of privacy of twitter users. The findings revealed that the perceptions of privacy of Twitter users in Saudi Arabia is affected by variables that include trust, age, gender, education, and experience in different ways. The study recommends that users characteristics are playing an important part in information sharing online, the need to undertake a broader as well as wider study that will include diverse and a large number of participants to gather as many views as possible.